2012
DOI: 10.1007/s00774-012-0350-8
|View full text |Cite
|
Sign up to set email alerts
|

Poncirin prevents bone loss in glucocorticoid-induced osteoporosis in vivo and in vitro

Abstract: Poncirin, a flavonoid isolated from the fruit of Poncirus trifoliata, possesses anti-bacterial and anti-inflammatory activities. However, the action of poncirin in bone biology is unclear. In this study, the in vivo and in vitro effects of poncirin in a glucocorticoid-induced osteoporosis (GIO) mouse model were investigated. Seven-month-old male mice were assigned to the following five groups: (1) sham-implantation (sham), (2) prednisolone 2.1 mg/kg/day (GC), (3) GC treated with 10 mg/kg/day of genistein, (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Citrus fruits contain abundant flavonoids such as Hesperidin, Naringin, Nobiletin, and Poncirin, which exhibit anticancer effect in different cancer cells [ 9 , 10 ]. Poncirin, the 7- O -neohesperidoside of isosakuranetin ( Figure 1 A), is a flavanone glycoside with bitter taste possessing various biological benefits such as antioxidant, anti-microbial, anti-inflammatory, and anti-cancer activities [ 11 , 12 , 13 ]. However, limited reports are available regarding anti-cancer effects of Poncirin and its molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus fruits contain abundant flavonoids such as Hesperidin, Naringin, Nobiletin, and Poncirin, which exhibit anticancer effect in different cancer cells [ 9 , 10 ]. Poncirin, the 7- O -neohesperidoside of isosakuranetin ( Figure 1 A), is a flavanone glycoside with bitter taste possessing various biological benefits such as antioxidant, anti-microbial, anti-inflammatory, and anti-cancer activities [ 11 , 12 , 13 ]. However, limited reports are available regarding anti-cancer effects of Poncirin and its molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies in vivo have shown GC administration to rats both histologically and histomorphometrically inhibits bone formation in the trabecular bone; particularly in the vertebrae [ 11 12 13 14 15 16 17 18 19 20 21 22 ]. In the other hand, it would reduce bone strength [ 12 15 21 22 ] and bone mineral density (BMD) as shown by BMD and other radiologic imaging techniques [ 11 13 16 19 21 23 24 25 ]. In addition, It would cause a decrease in biomarkers in the serum [ 13 15 16 17 24 25 ].…”
mentioning
confidence: 99%
“…In the other hand, it would reduce bone strength [ 12 15 21 22 ] and bone mineral density (BMD) as shown by BMD and other radiologic imaging techniques [ 11 13 16 19 21 23 24 25 ]. In addition, It would cause a decrease in biomarkers in the serum [ 13 15 16 17 24 25 ]. Eventual, GCs cause decrease in the molecular elements of bones as shown by the molecular biology techniques [ 14 17 18 20 22 25 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, clinical studies have shown that low-dose GC inhalatory therapy (8) or high-dose oral GC therapy, particularly with dexamethasone (DXM) (9) causes bone loss in humans. Briefly, the underlying molecular mechanisms responsible for GC-induced bone loss involve a decrease in bone formation directly by inhibiting osteoblasts from producing new bone and an increase in bone resorption by increasing osteoclast activity (10,11). In vitro studies demonstrated that GCs are capable of inducing the apoptosis of osteoblasts and osteocytes (3,12).…”
Section: Introductionmentioning
confidence: 99%